2017
DOI: 10.1080/07434618.2017.1375979
|View full text |Cite
|
Sign up to set email alerts
|

Augmentative and alternative communication practices: a descriptive study of the perceptions of South African speech-language therapists

Abstract: Speech-language therapists (SLTs) have direct contact with a wide variety of individuals who require augmentative and alternative communication (AAC) and they are therefore considered to have a primary role in the assessment, selection, and implementation of AAC symbols, techniques, aids, and strategies. Limited information is available with regard to SLTs" practices in the field of AAC, and there is a particular paucity of information about developing country contexts such as South Africa. The aim of this stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
34
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(36 citation statements)
references
References 36 publications
0
34
1
1
Order By: Relevance
“…For example, reliability and ease of editing were important considerations for both the current UK participants and their Canadian counterparts (Lindsay, 2010). In contrast, consideration of graphic representational forms seems to differ from those found in a recent South African study (Dada et al, 2017). The participants in this UK study favoured more abstract symbols for children with higher cognitive abilities, whereas South African SLTs favoured more iconic symbols that were easier to learn.…”
Section: Discussioncontrasting
confidence: 64%
See 2 more Smart Citations
“…For example, reliability and ease of editing were important considerations for both the current UK participants and their Canadian counterparts (Lindsay, 2010). In contrast, consideration of graphic representational forms seems to differ from those found in a recent South African study (Dada et al, 2017). The participants in this UK study favoured more abstract symbols for children with higher cognitive abilities, whereas South African SLTs favoured more iconic symbols that were easier to learn.…”
Section: Discussioncontrasting
confidence: 64%
“…The results showed that the specialist SLPs approached the AAC assessment differently for each of the two children; focusing on facilitating language development for the child with cerebral palsy, and on the purposes and motivation to communicate for the child with autism spectrum condition (ASC). Finally, Dada, Murphy, and T€ onsing (2017) conducted an online survey of 121 South African SLPs on their perceptions of their AAC prescribing practices. In contrast to the two previous studies (Dietz et al, 2012;Lund et al, 2017), Dada et al (2017) reported that most respondents indicated they worked in teams and used a combination of standardized assessment and functional communication tasks to inform their decisions.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Graphic representation stands out as the only language attribute ranked as having lower than average relative importance in this study. Recent studies suggest ambivalence towards the challenges or levels of cognitive difficulty associated with perceived levels of graphic representation (Dada, Murphy, & Tönsing, 2017). There is some evidence that more abstract symbols are favored for children with higher cognitive abilities, while in other contexts there was a preference to go for more iconic symbols that were easier to learn.…”
Section: Discussionmentioning
confidence: 99%
“…This profile is representative of speech-language therapists and AAC service providers in South Africa (cf. (Dada, Murphy, & Tönsing, 2017;Kathard & Pillay, 2013); however, it still complicates and limits service delivery to large proportions of the population -particularly those from African language backgrounds. Although the data obtained through the focus group may be a commentary on the current status quo in the field, it should be acknowledged that this status quo itself is biased and excludes specific sectors of the population who do not receive services and are therefore not considered in service providers' opinions -particularly clients who are from African language backgrounds.…”
Section: Limitationsmentioning
confidence: 99%